Persepsi Santri Terhadap Penerapan Podcast Sebagai Media Pembelajaran Bahasa Arab Berbasis Audio - Maghfiroh, Zaidatul Laili (STAI Hidayatut Thullab Kediri, 2022)
Arabic is a compulsory subject for santries in Islamic boarding schools. In learning Arabic in this digital era, technology has a big role to play. This is not limited to Islamic boarding schools which in fact have modern characteristics, namely the Syarif Hidayatullah Cyber ​​Islamic Boarding School. One of the innovations that can be done is by utilizing audio-based podcast learning media. This article aims to determine the santries' perception of the use of podcasts as an audio-based Arabic learning media. The data in this study were obtained from the results of field observations and questionnaires distributed, and the respondents who contributed were 92 santries. This study uses a descriptive approach with qualitative research methods. The data collection technique in this study was carried out by distributing questionnaires through Google forms to a number of Syarif Hidayatullah Cyber ​​Islamic Boarding School santries. Data analysis was carried out by grouping the average answer scores on the questionnaire, looking for the percentage of respondents' responses, and interpreting the results of respondents' responses based on percentages. The results of the study were that most of the santries knew and used podcasts. Podcasts are considered innovative as audio-based Arabic learning media. With the podcast, santries are aware of the importance of learning Arabic for their future.